Left atrial function in heart failure with preserved ejection fraction vs. aortic stenosis: evidence for atrial myopathy?. (8th February 2021) - Jin, X; Melle, JV; Voors, AA; Sim, DKL; Jaufeerally, FR; Lee, SSG; Soon, D; Loh, SY; Ding, ZP; Richard, MA; Lam, CSP; Ling, LH
Abstract: Funding Acknowledgements: Type of funding sources: None. Background and Aim: Left atrial (LA) enlargement and impaired LA function are frequently found in patients with heart failure with preserved ejection fraction (HFpEF). Whether these structural and functional LA abnormalities are a consequence of increased LA pressure or whether HFpEF patients have an intrinsic LA myopathy is unknown. We compared LA pressure, size and function between patients with HFpEF and aortic stenosis, as a comparator with LA pressure overload, as well as community-dwelling control subjects. Methods: Extensive echocardiographic assessments were performed in 219 patients with HFpEF (age 68 ± 11, 48% female), 173 patients with moderate to severe AS (age 69 ± 11, 55% female, aortic valve area index 0.55 ± 0.15 cm2/m2), and 219 controls (age 65 ± 9, 48% female, 42.2% hypertensive) Results: Compared to controls, both patients with HFpEF and AS had larger LV and LA size and worse LV systolic, diastolic and LA function. Compared with AS patients, HFpEF patients had smaller LA volume index (40.2 ± 19.4 vs. 44.5 ± 11.9 ml/m2 p = 0.01) but similar LV filling pressure estimated by E/e' (13.4 ± 4.8  13.4 ± 4.8, p = 0.12). Despite smaller LA volume index and similar LV filling pressure, HFpEF patients had remarkably poorer LA function compared to AS [reservoir GLS, 22.6 ± 10% vs 31.4 ± 10.1 (p < 0.001); contractile GLS, 15.8 ± 6.1% vs 17.5 ± 6.9 (p < 0.05); LASrs, 0.92 ± 0.35% vs 1.27 ± 0.41 (p < 0.001); LASre, -1.49 ± 0.65 vs -1.86 ± 0.67 (p < 0.001)]. The differences in  LA reservoir GLS and LASrs remained significant  after adjustment for atrial fibrillation, diabetes, coronary artery disease, LV ejection fraction and LV mass index. Conclusion: Patients with HFpEF had significantly worse LA function than patients with AS, despite similar LA pressure overload. These findings support the concept of an intrinsic LA myopathy in patients with HFpEF, beyond LA pressure overload.